ANALISIS PERAN BIMBINGAN KONSELING KRISTEN DALAM PEMBENTUKAN KARAKTER DAN KESEHATAN MENTAL REMAJA - Marthelda Salomina Wandauw; Leni Srigandi Salombe’; Mawar Malan Tasik; Lismayanti; Ristayani (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to analyze the role of Christian counseling in character formation and mental health in adolescents. Adolescence is a developmental phase vulnerable to various psychological problems and identity crises, thus requiring comprehensive support. The method used is a descriptive qualitative approach with data collection techniques through literature studies and analysis of relevant documents. The results of the study indicate that Christian counseling contributes significantly to shaping adolescent character through the internalization of faith values, such as honesty, responsibility, and love. Furthermore, this approach also plays a role in improving mental health through emotional management, strengthening self-concept, and providing meaning in life based on spirituality. Despite facing challenges in the modern era, such as the influence of technology and value pluralism, Christian counseling still has significant opportunities to develop through an adaptive and contextual approach. Thus, Christian counseling is an effective strategy in supporting the holistic development of adolescents.